The Impact of Christian Religious Education Management in Developing Children's Character in The Family - Darmin Usman Zega (Jurnal Abdimas, 2024)
Christian Religious Education management has a very important impact in fostering children's character in the family. It not only focuses on the formation of a child's religious beliefs, but also plays an important role in the formation of moral values and character. In the family environment, the management of Christian religious education implies several important components: teaching, training, modeling, monitoring the child's personal development, and creating a solid foundation for the formation of the child's character. This can be done through various methods, such as teaching the Bible, praying together, telling inspiring stories based on the truth of God's Word, participating in family and church worship activities. It also helps to encourage children to face various challenges and difficult situations experienced in daily life with a strong faith. Children can also make the right decisions when facing pressure, temptation, and even difficult circumstances. The overall role of Christian religious education management in the family has a huge impact on helping to develop children's character. This not only affects the child's behavior in the family environment, but also has an impact on social relationships and interactions with the wider community. Therefore, it is imperative for parents to be more diligent in implementing Christian education management to help their children grow into individuals who have the morality and responsibility of the Christian faith.